Physico-chemical properties of cervical mucus discharge and endocrine profile during oestrus and metoestrus period in crossbred dairy cows with and without metoestrual bleeding - M. Nisarga; K. Promod; L. Chacko; S. Promod; E.D. Benjamin (Journal of Veterinary and Animal Sciences, 2022)
The physicochemical properties of cervical mucus discharge (CMD), serum oestrogen and progesterone profiles during oestrus (day 0) and metoestrus (day 2) period in crossbred cows with (Group I, n=12) and without (Group II, n=12) history of profuse metoestrual bleeding were studied. Majority of group I cows exhibited clear and transparent CMD (83.33 per cent) with thin consistency (100 per cent), typical fern pattern (83.33 per cent), pH (7.58±0.12) and spinnbarkeit value of 12.64±0.50 cm during oestrus. However, during metoestrus all the cows (100 per cent) exhibited bloody CMD with thin consistency (66.67 per cent), ‘nil’ fern pattern (0.0 per cent), mean pH of 7.96±0.10 and mean spinnbarkeit value of 9.35±0.5 cm. In group I cows, the mean pH and spinnbarkeit values of CMD (7.96±0.10 and 9.35±0.5 cm, respectively) was significantly (p<0.01) higher than that of group II cows (7.64±0.07 and 7.75±0.30 cm, respectively) during metoestrus. The mean serum progesterone concentration of group I cows (1.61±0.55 ng/mL) was significantly (p<0.05) higher than that of group II cows (0.36±0.07 ng/mL) on day of oestrus. The mean serum oestradiol concentration of group I cow (6.85±0.53 pg/mL) was significantly (p<0.05) lower when compared to group II cows (8.48±0.49 pg/mL) during metoestrus. In conclusion, the physicochemical properties of CMD, serum progesterone and oestrogen profiles significantly altered in group I cows during oestrus and metoestrus which showed lower conception rate than that of group II cows.